Acquired generalized lipodystrophy under immune checkpoint inhibition. (9th August 2019) - Haddad, N.; Vidal‐Trecan, T.; Baroudjian, B.; Zagdanski, A.‐M.; Arangalage, D.; Battistella, M.; Gautier, J.‐F.; Lebbe, C.; Delyon, J.; ,
Summary: Immune checkpoint inhibitors are now the standard of care in the treatment of several types of cancer. Cutaneous immune‐related adverse events (irAEs) are usually of low grade and reversible, while endocrine irAEs are generally irreversible and managed with hormone replacement therapy. We report a 47‐year‐old patient, treated with the anti‐programmed cell death (PD)1 antibody pembrolizumab for a metastatic melanoma, who developed severe lipodystrophy after 10 months of treatment, characterized by the loss of subcutaneous fat tissue, central obesity and insulin resistance with a decreased leptin level. Histological analysis of a cutaneous biopsy revealed subcutaneous fat cell destruction associated with oedema, the presence of lipophages, and a CD3 + lymphocytic infiltrate involving the panniculus. This led to the diagnosis of anti‐PD‐1‐induced acquired generalized lipodystrophy, after ruling out differential diagnoses (i.e. genetic and systemic autoimmune diseases). No corticosteroids were introduced considering the high risk of inducing severe metabolic complications, and pembrolizumab was discontinued as complete response of the melanoma was achieved. However, after 12 months of follow‐up, lipodystrophy and its severe metabolic complications are still ongoing. What's already known about this topic? Anti‐programmed cell death (PD)1 agents are now a standard of care in the treatment of several cancers, including melanoma. Endocrine and cutaneous immune‐related adverse events (irAEs) are among the most frequent irAEs (14–30% and 30–40%, respectively) in patients treated with immune checkpoint inhibitors. What does this study add? Acquired generalized lipodystrophy can occur during anti‐PD1 therapy and is associated with severe metabolic complications. With the increase in anti‐PD1 prescription in several cancer types, clinicians must be aware of the whole range of irAEs that may occur. Abstract : Linked Comment: Hunter. Br J Dermatol 2020; 182 :276–277 .